Lifetime high occupational physical activity and total and cause-specific mortality among 320 000 adults in the NIH-AARP study: a cohort study. Issue 3 (1st November 2021) - Martinez Gomez, David; Coenen, Pieter; Celis-Morales, Carlos; Mota, Jorge; Rodriguez-Artalejo, Fernando; Matthews, Charles; Saint-Maurice, Pedro F
Abstract : Objectives: We examined the associations of history and duration in high occupational physical activity (OPA) with long-term total and cause-specific mortality. Methods: The sample included 322 126 participants (135 254 women) from the National Institutes of Health–AARP Diet and Health Study, established in 1995–1996. History and duration in high OPA were reported by participants. All-cause, cardiovascular, cancer and other cause mortality records available through 31 December 2011. Results: The prevalence of high OPA was 52.1% in men and 16.1% in women. During 13.6 years (SD, 3.3) of follow-up, 73 563 participants (25 219 women) died. In age-adjusted models, the risk of death was higher among men (HR 1.14, 95% CI 1.12 to 1.16) and women (HR 1.22, 95% CI 1.18 to 1.26) with a history of high OPA. However, these associations were substantially attenuated in women (HR 1.04, 95% CI 1.00 to 1.07, an 81.8% attenuation) and eliminated in men (HR 1.02, 95% CI 0.99 to 1.04, 85.7% attenuation) after multivariable adjustments. Similar important attenuation results were found when examining duration in high OPA, as well as using cause-specific deaths as the outcomes. Educational attainment and smoking patterns were the main contributors in the excess mortality among people working in highly physically active jobs in both men and women. Conclusion: Participating in high OPA was not consistently associated with a higher mortality risk, after adjustments for education and smoking factors. Workers in high OPA should be aware that they might not be getting all well-known health benefits of being physically active if they are only very active at work.